Molecular Docking studies on Andrographis echioides as a target for Diabetes Mellitus – An Insilco study - Nirubama K, Rubalakshmi G, Vijayakumar N, Vidhya M; Suriyavadhana M (International Journal of Advanced Science and Technology, 2020)
Diabetes mellitus is the group of metabolic diseases and now it is the third leading cause of death in humans. In the current study designing valuable antidiabetic drug was explored by using molecular docking techniques. Andrographis echioides is a unique medicinal plant of Acanthaceae family. It is habitually found in Tamilnadu, Kerala and Srilanka. The present study attempts to begin a relationship involving ethnopharmacological claims and bioactive constituents are in Andrographis echioides against all possible targets for diabetes during molecular docking for the dynamic goal. The process of molecular docking involves study of different bonding modes of one ligand with energetic cavities of target receptors protein aldose reductase (AR), and insulin receptor (IR) with help of docking software. It evaluates how small molecules called ligands (flavonoids) and the target macromolecule (aldose reductase enzyme) fit together. Both the receptors were docked with 17 bioactive compounds of Andrographis Echioides, From the outcome of docking score values on different receptors for antidiabetic activity, it has been found is that constituents, namely, 3, 4 Altrosan showed the preeminent docking results on about all the receptors, while the most important results were observed on AR. Insilco molecular docking provides essential indicator that can be used to plan new molecules with enhanced activity. The docking results have known enhanced insights into the progress of better aldose reductase inhibitor to treat diabetes associated secondary complications